Dimensions of Structure: A Review and Reappraisal - Blackburn, Richard S. (Academy of Management Review, 1982)
A review of empirical literature on the determination of structural dimensions reveals conceptual and methodological shortcomings that may have predetermined the outcomes of such research. To further the investigation of the structure domain, Q-analysis is proposed as an alternative research perspective. This procedure enhances the importance of the organizational participant in construct definition and reduces researcher biases in the resulting empirically derived dimensions.